Clinical and Electrical Evolution of “Pseudo” Spike–Wave Activation in Sleep EEG Patterns in Self-Limited Childhood Epilepsies - Neetha Balaram; Smita Balachandran; Abdul V Gafoor; SR Ratheesh (Annals of Indian Academy of Neurology, 2025)
The purpose of this study was to identify the pseudo spike–wave activation in sleep (SWAS) patterns in the electroencephalogram (EEG) of self-limited focal epilepsies of childhood (SeLFE) and study their clinical and electrical evolution. Sleep EEG and clinical data of children aged 2–12 years with SeLFE and pseudo-SWAS were collected retrospectively from our EEG database and were followed periodically every 6 months with clinical, EEG, and neurocognitive assessments. Nine children were identified and were grouped as follows: (a) pseudo-SWAS pattern caused by type 1 occipitofrontal spikes in five children, who had no clinical worsening on follow-up, and this pattern resolved within 3 years; (b) pseudo-SWAS pattern without occipitofrontal spikes in three children that was caused by diffusion of pre-existing focal spikes; and (c) pseudo-SWAS pattern induced by antiseizure medication in one child, which completely resolved on withdrawing the medication. Electro-clinical dissociation occurred in pseudo-SWAS, and none of them evolved to developmental and/or epileptic encephalopathy with SWAS. Identification of these patterns helps to avoid inadvertent use of antiseizure medications and immunomodulators.